Podejście psychologiczne, socjologiczne, komunikologiczne i prakseologiczne do oceny procesu komunikowania - Wiejak, Katarzyna; Sukiennik, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article shows the importance and necessity of undertaking research on evaluation of effectiveness of communication process. Communication is one of the most important activities of modern organisation. This aspect is not present in classical psychological, sociological and communicational theory. Praxiological perspective may lead to ways of increasing communication actions effectiveness using social sciences theory. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 290-298